THE REACTION OF IMMUNOCOMPETENT LIVER CELLS DURING CHEMICAL CASTRATION OF MALE RATS CAUSED BY THE INTRODUCTION OF TRIPTORELIN ACETATE - Rud, M.V.; Shepitko, V.I.; Stetsuk, Ye.V.; Akimov, O.Ye.; Vilkhova, O.V.; Skotarenko, T.A. (World of Medicine and Biology, 2021)
The purpose of our study was to elucidate the qualitative and quantitative changes in immunocompetent liver cells during chemical castration of male rats of central origin caused by the introduction of triptorelin acetate solution at different time intervals, to determine the sources of nitric oxide production as well as the effects of quercetin on morphological and quantitative changes of antigenpresenting liver cells. The morphological changes in the experimental groups with central testosterone deprivation and with its subsequent correction with quercetin on the 30th day of the experiment are identical and include signs of stromal ‒ vascular changes in the form of an increase in the thickness of the beam system and minor venous stasis with macrophage infiltration. Central 30 ‒ day deprivation of testosterone synthesis leads to a shift in the functioning of enzymes of the nitric oxide cycle in rat liver towards a predominance of the activity of inducible NO-synthase.